Perbedaan Hasil Belajar IPA-Fisika Menggunakan Model Problem Solving Dengan Model Pembelajaran Tipe Think, Pair, Share (TPS) Dikelas VII MTsN Tarusan Kabupaten Pesisir Selatan - Nurhasnah, Nurhasnah (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This research aims to determine differences in learning outcomes IPA-Physics students taught using models problem Solving with learning Model TPS mode and conventional learning. Hypothesis (H1) formulated in this study is the